Strategi Peningkatan Peran Pemangku Kepentingan Ditinjau dari Model Penta Helix dalam Pengelolaan Smart City Kota Semarang - Stg, Febrina (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Provinsi Sumatera Utara, 2024)
Smart City is an innovation implemented in Semarang City as an alternative solution to urban challenges and problems by integrating information and communication technology (ICT) based on the Internet of Things (IoT). The success of smart city implementation is inseparable from the role of stakeholders as development actors in driving innovation, public services, and investment in Semarang City as the economic center and economic growth of Central Java. This study aims to identify, map, and formulate the role of stakeholders in terms of the Penta Helix model, namely the government, private sector, academia, mass media, and the community, with the concept of collaboration in the management of Semarang Smart City Quick Wins based on the regulation of the mayor of Semarang Number 26 of 2018. The research method used is a qualitative descriptive method, consisting of primary data obtained through direct interviews (face-to-face) with key informants and secondary data obtained through literature studies and previous studies related to research topics. The data analysis technique uses stakeholder analysis to obtain a strong framework to determine the extent of stakeholders' roles in maximizing smart city implementation. This helps identify the complexity of relationships between parties, minimize risks, and create an environment that supports sustainable innovation in facing dynamic urban conditions and is adaptive to these changes. Knowing the problems and potentials substantially and technically can be a proposed strategy to increase the role of stakeholders, which in turn can be a policy recommendation for stakeholders to improve the quality of public services in Semarang City. Keywords: smart city; quick wins; Penta Helix model; collaboration; stakeholders